Correlation Between Hippocampus MRI Radiomic Features and Resting-State Intrahippocampal Functional Connectivity in Alzheimer’s Disease - Feng, Qi; Wang, Mei; Song, Qiaowei; Wu, Zhengwang; Jiang, Hongyang; Pang, Peipei; Liao, Zhengluan; Yu, Enyan; Ding, Zhongxiang (Frontiers in Neuroscience, 2019)
Alzheimer's disease (AD) is a neurodegenerative disease with main symptoms of chronic primary memory loss and cognitive impairment. The study aim is to investigate the correlation between hippocampal functional connectivity (FC) and MRI radiomic features in AD. A total of 67 AD patients and 44 normal controls (NC) were enrolled in this study. Using one method of resting-state functional MRI (rs-fMRI), the whole-brain FC with bilateral hippocampus as seed was performed, and the FC values were extracted from the bilateral hippocampus respectively. We observed that AD patients demonstrated disruptive FC in some brain regions in the left hippocampal functional network, including right gyrus rectus, right anterior cingulate and paracingulate gyri, bilateral precuneus, bilateral angular gyrus, and bilateral middle occipital gyrus. In addition, decreased FC was witnessed in some brain regions in the right hippocampal functional network, including bilateral anterior cingulate and paracingulate gyri, right dorsolateral superior frontal gyrus, and right precentral gyrus. Bilateral hippocampal radiomics features were calculated and selected respectively using A.K software. Pearson correlation analysis suggested that two gray level run-length matrix (RLM) radiomic features and one gray level co-occurrence matrix (GLCM) radiomic features weakly associated with FC values in the left hippocampus. However, there were no significant correlations between radiomic features and FC values in the right hippocampus. Compared with the NC group, the AD group showed abnormalities of FC level in the bilateral hippocampal functional network. This is a prospective study revealed the correlation between the MRI radiomic features and the rs-fMRI in AD patients.